(untitled) (Journal of Hama University, 2019)
The present study was carried out to investigate the prevalence of Ascaridia galli infections in commercial Farms of laying hens in the middle region of Syria. A total of 180 faecal samples out of 9 laying hens ﬂocks were examined using direct smear and concentration flotation method. The results showed that 78 samples out of 180 were infected with Ascaridia galli and the prevalence rate as a percentage was 43.3%. the prevalence rate in Hama was 44.16% while 41.6% in Homs. The prevalence rate for the positive samples ranging between 35%-55% in the infected flocks